First evidence of recombinant Myxomavirus (ha-MYXV) in European hare (Lepus europaeus) in the Czech Republic and Slovakia - Sedlák, Kamil; Mikulášková, Kateřina; Nagy, Alexander; Cukor, Jan; Príhodová, Pavla; Černíková, Lenka; Kostka, František; Václavek, Petr (Frontiers in Veterinary Science, 2026)
Recombinant myxoma virus (ha-MYXV) is an important causative agent of a fatal disease affecting hares (Lepus spp.). It was first identified in the Iberian Peninsula in 2018 and it subsequently spread to Western Europe during 2023–2024. Here, we report the emergence of this severe disease in the Czech Republic and Slovakia. The ha-MYXV was first detected in a European hare (Lepus europaeus) found dead in the Czech Republic on August 25, 2025. By the end of September, a total of 21 cases had been confirmed, 20 in European hares and one in a European rabbit (Oryctolagus cuniculus). In Slovakia, the virus was first detected in a hare found dead on October 9, 2025, followed by three additional cases. Our findings indicate the ongoing expansion of ha-MYXV, supported by evidence of cross-species transmission and an increasing geographic distribution to other Central European countries, with a projected fatal impact on European hare (Lepus europaeus) populations, as previously observed on the Iberian Peninsula.